Compound Heterozygous Mutations in PNKP Gene in an Iranian Child with Microcephaly, Seizures, and Developmental Delay. (15th April 2021) - Bitarafan, Fatemeh; Khodaeian, Mehrnoosh; Almadani, Navid; Kalhor, Alireza; Sardehaei, Elham Amjadi; Garshasbi, Masoud
Abstract: Background: Pathogenic variants within polynucleotide kinase 3′phosphatase ( PNKP ) gene cause microcephaly, seizures, and developmental delay (MCSZ) and ataxia-oculomotor apraxia type 4 (AOA4) disorders due to unrepaired DNA lesions. Methods: Whole exome sequencing was performed on a child with microcephaly, seizures, developmental delay, callosal dysgenesis on MRI, intellectual disability, speech disorder, hyperactivity, and ataxic gait. Results: Two heterozygous mutations in the PKNP gene, a novel intronic frameshift variant c.1298 + 33_1299-24del and a previously reported duplication, c.1253_1269dup; p.Thr424Glyfs*49 in exon 14 were identified. Both of these mutations affect the DNA kinase domain of PKNP. Conclusions: Our finding along with previous studies provide more evidence of the clinical heterogeneity of diseases caused by mutations in PNKP which makes its clinical diagnosis difficult and highlights the importance of genetic testing to unravel the cause of these diseases.